Applying standard independent verification and validation techniques within an agile framework: Identifying and reconciling incompatibilities. Issue 4 (3rd May 2019) - Dabney, James B.; Arthur, James D.
Abstract: Agile methods have gained wide acceptance over the past several years. They are now a standard management and execution approach for small‐scale system development projects. While Agile methods are not generally applicable to large multiyear and mission‐critical systems, hybrid Agile approaches are being developed to exploit the productivity improvements of Agile while retaining the necessary process rigor and coordination needs of these types of projects. From the perspective of Independent Verification and Validation (IV&V), however, adoption of these hybrid‐Agile frameworks is becoming problematic. Hence, we find it prudent to question the compatibility of conventional IV&V techniques with hybrid‐Agile practices. This paper documents investigation of relevant literature, the modification and adoption of Agile frameworks to accommodate the development of large scale, mission‐critical systems, and the compatibility of standard IV&V techniques within hybrid‐Agile development frameworks. Specific to the latter, we find that the IV&V techniques employed within a hybrid‐Agile process can be divided into three groups: early lifecycle techniques that are fully compatible with the hybrid frameworks, techniques that focus on tracing requirements, test objectives, etc, which are somewhat problematic, but can be tailored with modest effort, and techniques involving an assessment requiring artifact completeness, and consequently, are not compatible with hybrid‐Agile processes. We identify seven prominent techniques in this third category and propose alternative approaches that achieve similar goals and which can be applied within an Agile development process.